Islamic Apologetics in the Perspective of Religion and Development in the Digital Era - Iman Mukhroman; Yusuf Zainal Abidin; Aep Kusnawan; Rohmanur Aziz (UIN Sunan Gunung Djati Bandung, 2026)
Digital Islamic apologetics has become a new phenomenon in the relationship between religion and socio-cultural development. Digital space, especially YouTube, has become not only an arena for the dissemination of religious teachings, but also a platform for the formation of new religious authorities that influence solidarity and polarization in society. This study uses qualitative methods to analyze the structure of religious messages presented in two Bang Zuma videos uploaded on YouTube based on Robert Entman's (1993) framing analysis. Insights from Craig's (2008) apologetic epistemology consisting of five models: classical, evidential, Reformed epistemology, Presuppositional and Cumulative Case, as well as Berger & Luckmann's social constructionism model will be used to understand the emergence and development of digital faith reality. The findings show that Bang Zuma's apologetics integrates Craig's four main models: evidential (analysis of biblical texts and history), presuppositional (the Qur'an as the standard of absolute truth), classical (philosophical arguments against the Trinity), and reformed epistemology (tawhid as human nature), which emphasizes the rational and moral defense of Islam. This message study affirms Islam as a rational and ethical religion, but also fosters an oppositional logic of